Association for Caribbean Transformation Agricultural Marketing Information System (ACT-AIS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Association for Caribbean Transformation Agricultural Marketing Information System (ACT-AIS) designs customized information systems for farmers´ collectives for marketing their produce.